دور المراجعة الداخلية في تحسين إدارة النقدية والسيولة دراسة حالة لشركة الجيد لصناعة المواد الغذائية - أبوبكر سعيد الزنين (Surman Journal of Science and Technology, 2025)
Internal auditing plays a pivotal role in improving cash and liquidity management in companies, as this management is a fundamental element for ensuring financial stability and the ability to meet short-term obligations. This research paper aims to analyze how internal auditing contributes to enhancing the efficiency of cash management by evaluating financial processes, identifying risks, and proposing improvements to policies and procedures. The key roles of internal auditing include monitoring cash flows, analyzing liquidity-related risks, and ensuring compliance with financial regulations. Additionally, the paper highlights the use of modern technologies such as artificial intelligence and data analytics to enhance the effectiveness of internal auditing. Through a case study of a company that successfully improved its cash management thanks to internal audit recommendations, the paper provides practical recommendations to strengthen this role, including fostering interdepartmental collaboration, utilizing advanced analytical tools, and developing more effective financial policies. The paper concludes by emphasizing the importance of internal auditing as a strategic tool for achieving financial stability and mitigating risks associated with liquidity shortages.